2008
DOI: 10.1007/s12230-008-9001-y
|View full text |Cite
|
Sign up to set email alerts
|

Potato Yield and Tuber Set as Affected by Phosphorus Fertilization

Abstract: A 3 year field study on a loamy sand soil with medium to high soil test phosphorus (P) concentrations (25 to 33 mg kg −1 Bray P1) was conducted to evaluate the effect of P fertilizer rate, source, and timing, and starter nitrogen (N) rate on potato (Solanum tuberosum L. cv. Russet Burbank) yield, tuber size, tuber set, petiole P concentration, and P uptake and distribution within the plant. Nine fertilizer treatments compared banded P rates of 0, 37, 42, and 74 kg P ha −1 , the P sources monoammonium phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
73
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 13 publications
13
73
3
5
Order By: Relevance
“…Verifica-se que nos solos com maior disponibilidade de P a resposta da cultura ao P foi menor (Figuras 1a, 2a e 3a), apesar dos maiores teores de argila desses solos poderem também ter aumentado a adsorção dos íons fosfato no solo (Novais & Smyth, 1999). Outros autores também verificaram que as maiores respostas da batateira ao P ocorrem em solos com baixos teores de P disponível (Fernandes & Soratto, 2012), e que a aplicação de elevadas doses de P em solos com média e alta disponibilidade desse nutriente não aumenta a produtividade de tubérculos (Rosen & Bierman, 2008).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Verifica-se que nos solos com maior disponibilidade de P a resposta da cultura ao P foi menor (Figuras 1a, 2a e 3a), apesar dos maiores teores de argila desses solos poderem também ter aumentado a adsorção dos íons fosfato no solo (Novais & Smyth, 1999). Outros autores também verificaram que as maiores respostas da batateira ao P ocorrem em solos com baixos teores de P disponível (Fernandes & Soratto, 2012), e que a aplicação de elevadas doses de P em solos com média e alta disponibilidade desse nutriente não aumenta a produtividade de tubérculos (Rosen & Bierman, 2008).…”
Section: Resultsunclassified
“…Esta variável foi influenciada pelas doses de P apenas nos solos com baixa e média disponibilidade de P, ou seja, sob elevada disponibilidade de P o fornecimento desse nutriente via adubação não interferiu no crescimento dos tubérculos. Rosen & Bierman (2008) verificaram que sob alta disponibilidade de P, além da adubação fosfatada não aumentar o tamanho dos tubérculos, ela diminuiu o número de tubérculos de maior tamanho. No cultivo em solo com baixa disponibilidade de P, a massa média de tubérculos aumentou em 131% até a dose de 500 kg/ha de P 2 O 5 , e mesmo com esse aumento, Tabela 1.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Kang et al reported nitrogen deficiency induced potato tuberization without causing a significant retardation to the plant growth (Kang et al, 1996). Other nutritional element has been used to increase tuber set (Sanderson et al, 2003) and number (Rosen and Bierman, 2008) in potato plants is phosphorus. Rosen and Bierman (2008) reported that petiole P was positively correlated with number of potato tubers per plant.…”
Section: Introductionmentioning
confidence: 99%
“…Other nutritional element has been used to increase tuber set (Sanderson et al, 2003) and number (Rosen and Bierman, 2008) in potato plants is phosphorus. Rosen and Bierman (2008) reported that petiole P was positively correlated with number of potato tubers per plant. Intermittent reduction of solution pH could be a means to stimulate tuber production under hydroponic conditions.…”
Section: Introductionmentioning
confidence: 99%